Polonnaruwa civilization - Basnayake, H. T.; Hettige, Uda. (Colombo : Godage International Book Publishers, 2007)
With reference to Sri Lanka.
Includes bibliographical references (p. 243-249) and index.
Keywords: Polonnaruwa (Sri Lanka) -- Civilization